CORRELATION AND PATH COEFFICIENT ANALYSIS OF YIELD AND YIELD COMPONENTS IN CABBAGE (Brassica oleracea var. capitata L.) - Beyhan Kibar; Onur Karaağaç; Hayati Kar (Acta Scientiarum Polonorum: Hortorum Cultus, 2014)
This research was conducted to determine the interrelationships between yield and some yield components, and direct and indirect effects of such components on yield in cabbage (Brassica oleracea var. capitata L.). The experiment was carried out in a randomized complete block design with three replications using fourteen inbred lines of cabbage in Samsun, Turkey during 2011–2012. Correlation and path coefficient analysis were performed on 11 economic traits such as plant height, plant diameter, width of outer leaf, length of outer leaf, head weight, head diameter, head length, core length, diameter of interior stem, days to maturity and yield. A wide range of variation was observed among the cabbage genotypes for all the traits. It was found that all of the yield components except days to maturity and core length had highly significant and positive correlations with yield. The highest significant positive correlation was obtained between yield and head weight (r = 0.927**). Path coefficient analysis indicated that head weight (0.7139, 56.81%) had the highest positive direct effect on yield followed by head length (0.2265, 23.82%) and plant diameter (0.1907, 16.59%). As a result, head weight, head length, plant diameter, plant height, width of outer leaf, length of outer leaf, head diameter and diameter of interior stem could be effectively used as selection criteria in the breeding programme of cabbage varieties with high yielding, because these traits were the most important yield components affecting yield in cabbage.